Syed Alwi, seniman negara - Mohd. Ghouse Nasuruddin (Kuala Lumpur: Kementerian Kebudayaan, Kesenian dan Warisan Malaysia, 2005)
Biography of Syed Alwi, a Malaysian playwright; includes some of his works
Includes bibliographical references (p. 88-97)
Keywords: Syed Alwi Syed Hassan, -- 1930-; Dramatists, Malay; Screenwriters -- -- Malaysia; Malay drama; Malaysian drama (English)